Teacher Performance Incentives and Student Outcomes - Randall Eberts; Kevin Hollenbeck; Joe Stone (W.E. Upjohn Institute for Employment Research, 2000)
This paper reviews the evidence on the effectiveness of individual merit pay systems for teachers on student achievement, and it presents new empirical results based on a system established within a collective bargaining environment. While many merit pay systems have been established in school districts across the U.S., very little empirical evidence concerning their influence on student achievement exists. A natural experiment arose in a county in which one high school piloted a merit pay system that rewarded student retention and student evaluations of teachers while another comparable high school maintained a traditional compensation system. A difference-in-differences analysis implies that this system had no effect on grade point averages, reduced the percentage of students who dropped out of courses, reduced average daily attendance, and increased the percentage of students who failed. The outcomes of this merit pay system illustrate the difficulty of instituting such a compensation system in schools. The goal of the system was to increase student retention. A student was considered to be retained in a class if the student was present during a randomly selected day of the last week of classes. The system "worked" by this measure because the school experienced a significant reduction in course noncompleters. However it is not clear that this measure was correlated with student achievement or even average attendance, and indeed, neither of these outcomes were improved.
Keywords: I2; J3; J5; 330; merit pay; teachers; student achievement; Eberts; Hollenbeck; Stone